2017
DOI: 10.1186/s41241-017-0050-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of factors associated with hypoxia and lipid metabolism in patients with colorectal cancer

Abstract: Background: Colorectal cancer (CRC) is a neoplasia with high incidence and mortality rates. It had been suggested that the inflammatory response is an important CRC prognostic factor. The disordered and accelerated proliferation of neoplastic cells decreases the oxygen and nutrient supply, generating a microenvironment characterized by hypoxia, necrosis and inflammation. This study aimed to evaluate the impact of factors associated with hypoxia, such as HIF1A (hypoxia-inducible factor 1-alpha) and VEGF (vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Likewise, in the recent study conducted by authors’ group, the mutational status of BRAF or KRAS was not associated the prognosis of CRC [27]. For HIF , TP53 and TYMS , there are studies which reported the expression of the genes are not related to the prognosis of OS of CRC [28–30]. In this study, we also found that HIF , TP53 and TYMS were not associated with OS or DFS (Additional file 1: Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in the recent study conducted by authors’ group, the mutational status of BRAF or KRAS was not associated the prognosis of CRC [27]. For HIF , TP53 and TYMS , there are studies which reported the expression of the genes are not related to the prognosis of OS of CRC [28–30]. In this study, we also found that HIF , TP53 and TYMS were not associated with OS or DFS (Additional file 1: Table S4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increased palmitate synthesis, CRC exhibits enhanced FA elongation [48]. Upregulation of other lipid metabolism genes, including PPARG and ACSL1, are correlated with poor prognosis in CRC [49, 50]. Silencing genes encoding sterol regulatory element-binding proteins (SREBPs) 1 and 2, which are transcription factors critical for lipogenesis, inhibited CRC growth in vitro and in xenograft models [51].…”
Section: Lipid Biosynthesismentioning
confidence: 99%
“…Recent studies have largely noticed the significant role of fatty acids (FAs) in the progression and development of different forms of cancers ( 8 9 10 11 ). The expression levels of different enzymes involved in the metabolism of FAs, such as FA synthase and acyl-CoA synthetase long-chain-FA-CoA ligase 1 (ACSL1), have been suggested to influence the survival, invasion, and metastasis of CRC cells and play a significant role in carcinogenesis of colorectal cancer ( 12 13 14 15 ). CRC patients with higher tumor stages have shown higher serum levels of FA synthase enzyme ( 12 ).…”
Section: Introductionmentioning
confidence: 99%